Influence of diet and abiotic factors on the survival and reproduction of calanoid copepod Pseudodiaptomus annandalei / Fatin Fatihah Abd Aziz - Fatin Fatihah , Abd Aziz (2020)
The calanoid copepod, Pseudodiaptomus annandalei, due to its good nutritional value and significance as a natural diet of many tropical fish, is a superior live feed for marine fish larvae. Fish larvae needs a sustainable supply of good quality live feed for optimal growth and survival. Aims of this study were to investigate the effects of (1) marine mircroheterotrophs grown in palm oil mill effluent (POME) as copepod diet and (2) abiotic factors i.e. salinity (ppt), temperature (˚C), pH, photoperiod and light intensity on the survival and nauplii production of P. annandalei. Both biotic and abiotic experiments were conducted with the initial stocking density of fifty copepod nauplii stage I in 250 ml of sterile 15 ppt brackish water and nauplii were cultured in water baths under controlled condition. Each treatment was conducted in triplicates with a completely randomized design. Survival and reproduction of P. annandalei were determined every 2-day intervals for a duration of 14 days. P. annandalei fed on a mixed diet of 75% POME grown Shewanella algae (POME-SA) and 25% POME-grown Aurantiochytrium limacinum (POME-AL) had significantly (p < 0.05) higher survival (71.3±11.6%) and nauplii production on day 8 (27±1.2 nauplii) compared to other POME-based diets tested and a commercial microalgae product Nannochloropsis oculata. Salinities of 5, 15, 25 and 35 ppt had no effect on the survival of P. annandalei (p > 0.05) but influenced F2 nauplii production. The highest nauplii density was recorded at 15 ppt (103±48.8 nauplii) on day 14. The survival of P. annandalei was affected by temperature (p < 0.05) where 26˚C gave the highest survival (day 8: 85.3±4.7% and day 14: 58.7±9.6%) compared to those cultured at other temperatures (28˚C to 36˚C). In contrast, significant nauplii production recorded at 28˚C (42±12.4 nauplii). The survival of P. annandalei was affected by pH (p < 0.05) where 49.3±3.7% survival was recorded at pH 8 on last day but the nauplii production was not significant among treatments. Photoperiod did not affect the survival and nauplii production of P. annandalei where 82.0±11.4% survival and 11±4.0 nauplii was recorded at 12h light: 12h dark. The light intensity of 4.05 µmol/m2/sec gave the highest survival of P. annandalei (86.7±2.4%) compared to other treatments tested. No variations between treatments were detected for sex ratio and body growth in salinity, pH, photoperiod and light intensity experiments except for feed. At a larger scale experiment (1L tank), the survival of P. annandalei was high and maintained above 70% through experiment. Fatty acid analysis shows that a consortium of POME grown SA and POME-grown AL biomass contained 0.80±0.01% of docohexanoic acid (DHA) whilst P. annandalei fed on this mixed diet contained high amount of arachidonic acid (ARA) (0.91±0.35%), eicosapentaenoic acid (EPA) (4.36±0.02%) and DHA (7.21±0.06%). As conclusion, a mixed diet of POME-grown SA and POME-grown AL is the most suitable diet for mass culturing P. annandalei in captivity, incorporating the optimal culture conditions of 15±1 ppt salinity, 26.0±1.0 oC, pH 7-8, 12h light: 12h dark photoperiod and light intensity of 4.05 µmol/m2/sec.